Adult Learning in Innovative Organisations. (June 2016) - Sutherland Olsen, Dorothy
Abstract: The relationship between learning and innovation has been a central theme in studies of innovation (Fagerberg et al., 2005, Borras & Edquist, 2014, Lundvall & Johnsen, 1994). Studies of the workplace have also claimed a relationship between skills or training and a firm's ability to innovate (Toner, 2011). Recent studies of innovation in European firms (Arundal et al ., 2007) included surveys on organisational contexts and suggested that some organisational forms were especially conducive to learning and innovation. Studies of the learning context or of training and skills development often refer to, or make assumptions about learning, without explaining who is learning or how this learning is occurring. This article supplements some of these earlier surveys by carrying out in‐depth qualitative studies of learners in innovative organisations in Norway. The organisation of activities and the learning environments are analysed. This is supplemented by information on local HRM practice and strategies for skills development and training. The data include information on formal and informal learning of participants working within product development. We then discuss how these workers draw upon their learning in their everyday work and how their everyday work provides the opportunity for new learning. By linking HRM and innovation, this article offers a novel way of studying adult learning in the workplace and adds to our understanding of how it contributes to economic success.